Pengembangan Potensi Desa Wisata Melalui Pelatihan Homestay di Desa Cipasung, Kuningan - Sembiring, Vienna Artina; Taviprawati, Ervina; Darsiah, Anis (Jurnal Pemberdayaan Pariwisata; Vol 2 No 1 (2020): Jurnal Pemberdayaan Pariwisata, 2020)
The tourism village is a rural area that has several special characteristics to become a tourist destination. One of the villages that develops tourist villages to empower their communities is the village of Cipasung, Kuningan. With the potential of tourism attraction is the Darma Reservoir, Based on the results of a survey and cooperation carried out by the Community Service of STP Trisakti with partners, homestay training is conducted to the community in the village of Cipasung. The method used Observation Method, Socialization Method, Discussion Method. which numbered 26 people. Training and counseling were conducted at the BUMDES office in Cipasung village. On 09 - 11 December 2019. Homestay training is carried out to improve facilities, so that homestay hygiene is maintained, the host can provide good servants to guests who stay overnight at the homestay.